Karakteristik Probiotik Bakteri Fakultatif Mixotrofik yang Diisolasi dari Tambak Udang - Ardiansyah, Ardiansyah; Jaya, Andi Asdar; Amrullah, Amrullah; Dahlia, Dahlia; Indrayani, Indrayani (Universitas Sulawesi Barat, 2021)
ABSTRACT: The shrimp farming industry continuously requires new technology in an effort to increase production output. Probiotics are non-pathogenic microorganisms, non-toxic, and without any adverse side effects when administered to aquatic organisms. Mixotrophic facultative bacteria isolated from intensive shrimp ponds are able to decompose ammonia and hydrogen sulfide in pond water. However, the potential of mixotrophic facultative bacteria to become probiotics still needs to be evaluated. The aim of this study was to evaluate the potential of mixotrophic facultative bacteria in producing extracellular proteolytic, amylolytic and lipolytic. Data obtained in the form of the enzyme activity from four selected isolates of facultative mixotrophic bacteria were statistically analyzed using SPSS. The test results showed that isolates AOB1 isolates did not have extracellular proteolytic activity, AOB1, AOB13, AOB28 isolates had proteolytic and lipolytic activities, while isolates SOB31 had proteolytic, amylolytic, and lipolytic activities. SOB31 isolate showed the largest proteolytic, amylolytic, and lipolytic activity based on the resulting clear zone. ABSTRACT: Industri budidaya udang senantiasa membutuhkan teknologi baru dalam upaya peningkatan hasil produksi. Probiotik adalah mikroorganisme nonpatogenik, tidak beracun dan tanpa efek samping yang merugikan bila diberikan pada organisme akuatik. Bakteri fakultatif mixotrofik yang diisolasi dari tambak udang intensif mampu menguraikan amonia dan hidrogen sulfida dalam air tambak. Namun potensi bakteri fakultatif mixotrofik un menjadi probiotik masih perlu dievaluasi. Tujuan penelitian ini adalah untuk mengevaluasi potensi bakteri fakultatif mixotrofik dalam menghasilkan proteolitik, amilolitik dan lipolitik ekstraseluler. Penelitian ini menggunakan metode desriptif berupa aktivitas enzimatis empat isolat terpilih bakteri fakultatif mixotrofik. Hasil uji menunjukkan bahwa isolat AOB1 tidak memiliki aktivitas proteolitik ekstraseluler, isolat AOB13, AOB28 mempunyai aktivitas proteolitik, amilolitik, dan lipolitik. Isolat SOB31 memiliki aktivitas proteolitik, amilolitik dan lipolitik terbesar berdasarkan zona bening yang dihasilkan.